Mycotoxin Contamination Management Tools and Efficient Strategies in Feed Industry - Cheli, Federica (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Mycotoxins represent a significant issue for the feed industry and the safety of the feed supply chain, with an impact on human health, animal health and production, economies, and international trade. The globalization of the trade in agricultural commodities and the lack of legislative harmonization have contributed significantly to the discussion about the awareness of mycotoxins entering the feed/food supply chain. The feed industry is a sustainable outlet for food processing industries, converting byproducts into high-quality animal feed. Mycotoxin occurrence in food byproducts from different technological processes is a worldwide topic of interest for the feed industry, aiming to increase the marketability and acceptance of these products as feed ingredients and include them safely in the feed supply chain. Since mycotoxin contamination cannot be completely prevented pre- or post-harvest, the modern feed industry needs new tools for monitoring and managing the risk of mycotoxins and strategies to prevent and reduce mycotoxins in compound feed manufacturing. The aim of this Special Issue book was to bring together a collection of valuable articles with innovative ideas for a sustainable and competitive feed industry.